Civil War A to Z a young readers' guide to over 100 people, places, and points of importance - Bolotin, Norm, 1951- (New York : Dutton Children's Books, 2002)
Alphabetically arranged articles present over 100 people, places, and points of importance of the Civil War.
Includes bibliographical references (p. 139-142).
BL 07/02, SJ 07/02, KK 06/01/02
0812
Keywords: United States -- History -- Civil War, 1861-1865 -- Encyclopedias, Juvenile; United States -- History -- Civil War, 1861-1865 -- Encyclopedias